Evaluating Functional Outcome of Oblique Cut across Mentum in Advanced Oral Squamous Cell Carcinoma - Shomes Mozumder; Shilpi Agrawal; Aniruddha Dam; Anup Kumar Bhowmick; Ishita Sinha (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: